Changing teacher professionalism [ international trends, challenges, and ways forward - Gewirtz, Sharon , 1964- (Routledge, 2009)
Significant changes in the policy and social context of teaching over the last 30 years have had substantial implications for teacher professionalism. This collection of work by leading international scholars in the field makes a unique contribution to understanding both how these changes are impacting on teaching and how teachers might change their practice for the better